MODELING THE LEVEL OF COMPETITIVENESS OF INSURANCE COMPANIES - Головко, Олена; Гнип, Наталія; Бакланов, Ерік (Socio-economic relations in the digital society, 2019)
In the article reviewed the necessity of assessing the level of competitiveness of insurance companies. Identified factors that aff ect competitiveness and insurers activity taking into account them in econometric models. By means of coefficients of regression of fictitious variables factors that have a signifi cant impact on the insurance company's competitiveness: payments, gross premiums are determined. We combine all insurance companies in a single set and estimate the regression with diff erentiated coefficients, respectively, forming the fictitious variables of the slope and intersection. According to the position of the insurance company in the rating, we introduce the following fictitious variables: 1 — for an insurance company with a high level of insurance payments; 0 — for insurance companies with insufficient level of insurance payments. A multi-factor regression model and a variance analysis and their comparison are constructed that are statistically significant and adequate. The model is checked for absence of autocorrelation, and can be used as predicted and to assess the state of the insurance company in the insurance market.
Keywords: insurance company; competitiveness; payout; gross premiums; modeling